Abnormal Sleep, Circadian Rhythm Disruption, and Delirium in the ICU: Are They Related? - Daou, Marietou; Telias, Irene; Younes, Magdy; Brochard, Laurent; Wilcox, M. Elizabeth (Frontiers in Neurology, 2020)
Delirium is a syndrome characterized by acute brain failure resulting in neurocognitive disturbances affecting attention, awareness, and cognition. It is highly prevalent among critically ill patients and is associated with increased morbidity and mortality. A core domain of delirium is represented by behavioural disturbances in sleep-wake cycle probably related to circadian rhythm disruption. The relationship between sleep, circadian rhythm and intensive care unit (ICU)-acquired delirium is complex and likely bidirectional. In this review, we explore the proposed pathophysiological mechanisms of sleep disruption and circadian dysrhythmia as possible contributing factors in transitioning to delirium in the ICU and highlight some of the most relevant caveats for understanding the relationship between these complex phenomena. Specifically, we will (1) review the physiological consequences of poor sleep quality and efficiency; (2) explore how the neural substrate underlying the circadian clock functions may be disrupted in delirium; (3) discuss the role of sedative drugs as contributors to delirium and chrono-disruption; and, (4) describe the association between abnormal sleep-pathological wakefulness, circadian dysrhythmia, delirium and critical illness. Opportunities to improve sleep and readjust circadian rhythmicity to realign the circadian clock may exist as therapeutic targets in both the prevention and treatment of delirium in the ICU. Further research is required to better define these conditions and understand the underlying physiologic relationship to develop effective prevention and therapeutic strategies.